2017
DOI: 10.1002/cne.24336
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from the anatomical effects of long‐term monocular deprivation in cat lateral geniculate nucleus

Abstract: Monocular deprivation (MD) imposed early in postnatal life elicits profound structural and functional abnormalities throughout the primary visual pathway. The ability of MD to modify neurons within the visual system is restricted to a so-called critical period that, for cats, peaks at about one postnatal month and declines thereafter so that by about 3 months of age MD has little effect. Recovery from the consequences of MD likewise adheres to a critical period that ends by about 3 months of age, after which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 73 publications
4
44
0
Order By: Relevance
“…These limitations notwithstanding, results of these studies demonstrate the potential for recovery at ages not responsive to typical treatments. In a recent study using cats, temporary inactivation of retinal ganglion cells in the fellow eye using tetrodotoxin (TTX), FIGURE 1 | Summary of data from Duffy et al (2018) that examined the recovery of neuron soma size (open circles) and neurofilament labeling (closed circles) in the lateral geniculate nucleus of monocularly deprived cats. Six weeks of monocular deprivation (MD) started at the peak of the critical period for plasticity produced a large deprivation effect with deprived neurons rendered about ∼35% smaller than neurons connected to the non-deprived eye, and deprived layers showing a ∼55% reduction in the density of neurofilament-positive neurons.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations notwithstanding, results of these studies demonstrate the potential for recovery at ages not responsive to typical treatments. In a recent study using cats, temporary inactivation of retinal ganglion cells in the fellow eye using tetrodotoxin (TTX), FIGURE 1 | Summary of data from Duffy et al (2018) that examined the recovery of neuron soma size (open circles) and neurofilament labeling (closed circles) in the lateral geniculate nucleus of monocularly deprived cats. Six weeks of monocular deprivation (MD) started at the peak of the critical period for plasticity produced a large deprivation effect with deprived neurons rendered about ∼35% smaller than neurons connected to the non-deprived eye, and deprived layers showing a ∼55% reduction in the density of neurofilament-positive neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, spatial acuity in the deprived eye is undetectable 25 following cMD initiated at eye opening (Eaton et al, 2016). Additionally, following 26 prolonged monocular deprivation, neurons in the dorsal lateral geniculate nucleus 27 (dLGN) that project to deprived binocular visual cortex have lower metabolism (Kennedy 28 et al, 1981) and smaller somata (Duffy et al, 2018). Chronic monocular deprivation 29 (cMD) also significantly decreases the density of dendritic spines on pyramidal neurons 30 in deprived V1b (Montey and Quinlan, 2011) and results in a 60% decrease in the 31 thalamic component of the visually evoked potential (VEP, ( Montey and Quinlan, 32 2011)).…”
Section: Introduction 16 17mentioning
confidence: 99%
“…Based on the experimental results, VIP undeniably has a therapeutic effect on the visual nervous system. Some studies have found that LGBd function in form-deprived amblyopic kittens can be partially restored after the sensitive period of visual development [40], which is worthy of our next study. LGBd, increased the expression of VIP, shortened the latency of the P100 wave and increased its amplitude in amblyopic eyes.…”
Section: Vip Immunohistochemistrymentioning
confidence: 74%